2023
DOI: 10.1021/acsnano.3c03005
|View full text |Cite
|
Sign up to set email alerts
|

Click-Reaction-Mediated Chemotherapy and Photothermal Therapy Synergistically Inhibit Breast Cancer in Mice

Abstract: The development of functional materials for tumor immunogenicity enhancement is desirable for overcoming the low therapeutic efficiency and easy metastasis during tumor treatments. Herein, the thermoresponsive nanoparticles composed of photothermal agent (PTA) and click reactive reagent are developed for enhanced immunotherapy application. A Ni-bis(dithiolene)-containing PTA with intense near-infrared absorption and efficient photothermal conversion is developed for thermoresponsive nanoparticles construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 54 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…ICD could release TAAs and DAMPs for priming the downstream immune responses. [ 28,29 ] Thus, we investigated adenosine triphosphate (ATP) and high mobility group box 1 protein (HMGB1) releasing, two key DMAPs for ICD effects, by ATP assay kit and ELISA analysis, respectively. We first confirmed that SAB could not induced ICD at selected concentrations (Figures S9 and S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…ICD could release TAAs and DAMPs for priming the downstream immune responses. [ 28,29 ] Thus, we investigated adenosine triphosphate (ATP) and high mobility group box 1 protein (HMGB1) releasing, two key DMAPs for ICD effects, by ATP assay kit and ELISA analysis, respectively. We first confirmed that SAB could not induced ICD at selected concentrations (Figures S9 and S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the phototherapeutic effect of PYT NPs on tumor cells was assessed with standard cell counting kit-8 (CCK-8) assays (Fig. 3 a) in vitro [ 45 , 46 ]. In order to investigate the biological safety of PYT NPs, dark toxicity experiments of PYT NPs (at 0–50 μg mL −1 ) for three tumor cell lines, including 4T1, HeLa and B16F10, were investigated (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photothermal therapy (PTT) involves irradiation of light-absorbing agents accumulated in the tumor with light to convert optical energy into heat for thermal ablation of cancer cells. Theoretically, photothermal agents are non-toxic in the dark, but turn to be toxic to tumor cells upon the local applied light, leading to high treatment efficacy for all types of tumors with few side effects [ 7 12 ]. However, conventional photothermal therapy alone is not sufficient to completely eradicate tumors, leaving residual tumor margins and resulting in tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%